Critical Factors in Young People’s Use and Non-Use of AI Technology for Emotion Regulation: A Pilot Study - Junyu Wang; Hongying Tang; Siu-Shing Man; Yingwei Chen; Shuzhang Zhou; Hoi-Shou (Alan) Chan (Applied Sciences)
Emotional difficulties are increasingly prevalent amongst young people, yet the use of AI technology for emotion regulation remains limited. This study aimed to identify young people’s attitudes toward AI technology for emotion regulation and to analyse the factors influencing their decision to use or not use AI technology. Forty participants from China, comprising twenty males and twenty females, with a mean age of twenty-five, took part in the study. Data were collected through semi-structured face-to-face interviews and were analysed using NVivo 11 software. Grounded theory techniques and a three-stage coding approach were used to categorise the data. The grounded theory model demonstrated that user behaviours are influenced by three contextual factors: personal, technological and environmental contexts. Key influencing factors for user behaviours include fulfilling utilitarian, hedonic and social value needs such as perceived usefulness, ease of use, trust, positive emotions, interest, social perception, high value, convenience and privacy protection. This study offered theoretical insights and practical recommendations for designing and developing AI technology aimed at emotion regulation in youth populations.